Heat-conducting sealant and preparation method thereof

By introducing modified thermal fillers and toughening agents into the epoxy resin sealant, the problems of brittleness and insufficient conductivity of the epoxy resin sealant are solved, and the efficient thermal conductivity, high temperature resistance and toughening properties of the thermal sealant are achieved.

CN119823691APending Publication Date: 2025-04-15SUZHOU DONGCHENGXIN ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046258.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Epoxy resin sealants have problems in application, such as brittle quality, low toughness, high temperature resistance and poor wear resistance, and their conductive properties are not sufficient to meet the needs of the current industry.

Method used

A method of preparing a thermally conductive sealant is adopted, including a combination of an epoxy resin, a diluent, a thermal filler, a thixotropic agent, a curing agent and a modified toughening agent. Thermal conducting fillers are prepared by modification of silicon carbide, graphene oxide and nanodiamond, and the modified toughening agent is prepared by reactions of ammonia, formaldehyde and epoxychlorohydrin to form an interpenetrating network structure to improve toughness and impact resistance.

Benefits of technology

It achieves good toughening effect of thermally conductive sealants, reduces brittleness, and has excellent thermal conductivity and high temperature resistance, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238513140000101
    Figure BDA0005238513140000101
Patent Text Reader

Abstract

The invention relates to a heat-conducting sealant and a preparation method thereof, and belongs to the technical field of high polymer materials. The heat-conducting sealant comprises the following components in parts by weight: 50-95 parts of epoxy resin, 1-3 parts of a diluent, 10-30 parts of a heat-conducting filler, 2-10 parts of a thixotropic agent, 8-25 parts of a curing agent and 1-4 parts of a modified toughening agent, nano-diamond in the heat-conducting filler provides a good condition for heat conduction, sealant pores are filled, interface bonding of the filler and resin is enhanced, silicon carbide is dispersed in a resin matrix, a heat-conducting network chain is formed, and the heat-conducting property is improved; a maleimide group of the modified toughening agent and epoxy resin form a network structure, stress concentration under the action of external force is relieved, the maleimide group and hydroxymethyl cooperate to promote resin curing, and a polyurethane single soft and hard segment structure and a high-temperature-resistant oxazolidinone ring enhance toughness and inhibit crack propagation; the heat-conducting sealant prepared by the invention not only has a good toughening effect and reduced brittleness, but also has excellent heat-conducting and high-temperature-resistant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a heat-conducting sealant and a preparation method thereof. Background Art

[0002] Epoxy resin is widely used in the fields of construction, automobiles and electronic components due to its excellent adhesion, functionality, mechanical strength and bonding force. It is used as a sealant to achieve sealing, dustproofing, shock absorption and fixation.

[0003] However, with the continuous advancement of science and technology and the development needs of the industry, the limitations of epoxy resin glue have gradually emerged, including brittleness, low toughness, poor high temperature resistance and wear resistance, which limit its application range. The hardness of the cured epoxy resin is enhanced due to the highly cross-linked three-dimensional network structure, which is easy to cause stress concentration and become very brittle and hard. In addition, although epoxy resin glue has certain conductive properties, with the increase of actual application needs, the conductive properties of epoxy resin glue itself no longer meet the needs. Therefore, modifying these deficiencies to expand the application field of conductive sealants has become an important direction for the current development of the industry. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a thermally conductive sealant and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A heat-conductive sealant, comprising the following raw materials in parts by weight: 50-95 parts of epoxy resin, 1-3 parts of diluent, 10-30 parts of heat-conductive filler, 2-10 parts of thixotropic agent, 8-25 parts of curing agent, and 1-4 parts of modified toughening agent;

[0007] The diluent is butyl glycidyl ether;

[0008] The thixotropic agent is hydrated aluminum silicate;

[0009] The curing agent is 4,4'-diaminodiphenylmethane.

[0010] The thermally conductive filler is prepared by the following method:

[0011] Step A1: Silicon carbide and isopropanol were mixed evenly, and after ultrasonic peeling for 12 hours, centrifuged at 2000 r / min for 15 minutes to obtain a mixture;

[0012] Further, the usage ratio of silicon carbide and isopropanol is 2-4 g: 200-300 mL;

[0013] Step A2: polydimethyldiallylammonium chloride and graphene oxide were mixed evenly, stirred at room temperature for 12 hours, centrifuged at 10000 r / min for 10 minutes, washed, and then slowly added the mixture dropwise for 1 hour, centrifuged at 2000 r / min for 10 minutes, and freeze-dried to obtain a pre-product;

[0014] Further, the dosage ratio of polydimethyldiallylammonium chloride, graphene oxide, and the mixture is 300-400 mL: 0.4-0.6 g: 4.1-9.5 g;

[0015] Step A3: Mix concentrated sulfuric acid, concentrated nitric acid and nano-diamonds, heat and stir in a water bath at 75°C for 24 hours to obtain pretreated nano-diamonds; then disperse the pre-product in NaOH and stir for 12 hours, add 3-aminopropyltriethoxysilane and ethanol to mix, adjust the pH to 5, stir under magnetic suspension at 65°C for 8 hours, then add pretreated nano-diamonds, ultrasonically treat for 2 hours, wash and dry to obtain a thermal conductive filler;

[0016] Furthermore, the usage ratio of concentrated sulfuric acid, concentrated nitric acid, nanodiamond, pre-product, NaOH, 3-aminopropyltriethoxysilane and ethanol is 10.3-12.1 mL: 3.4-4 mL: 5-9 g: 6-8 g: 9-12 g: 0.2 mL: 5-15 mL.

[0017] The modified toughening agent is prepared by the following method:

[0018] Step B1: maleic anhydride is placed in a flask, sealed and ammonia is introduced, when cooled to room temperature, the introduction of ammonia is stopped, and the temperature is raised to 180°C for reaction for 6 hours, and after cooling to room temperature, tetrahydrofuran, formaldehyde and sodium hydroxide are added and mixed evenly, and the mixture is reacted at 30°C for 4 hours, rotary evaporated, washed, centrifuged, tetrabutylammonium bromide and epichlorohydrin are added and mixed, ultrasonicated for 1 hour, and then NaHCO3 is added, and the mixture is stirred in an oil bath at 90°C for 12 hours, filtered, rotary evaporated, washed, centrifuged, and dried at 45°C for 24 hours to obtain an intermediate;

[0019] Further, the dosage ratio of maleic anhydride, tetrahydrofuran, formaldehyde, sodium hydroxide, tetrabutylammonium bromide, epichlorohydrin, and NaHCO3 is 0.362-0.381 g: 3.58-3.63 g: 0.08-0.1 g: 0.225-0.32 mL: 0.2 mL: 5 g: 0.2 g;

[0020] Step B2: dehydrating the poly(p-phenylene ether sulfone), and evacuating the mixture under reduced pressure at 110° C. for 2 h, cooling the mixture to 60° C., adding toluene and toluene diisocyanate under nitrogen protection, mixing the mixture evenly, and reacting the mixture at 80° C. for 2 h to obtain a prepolymer;

[0021] Further, the usage ratio of poly(p-phenylene ether sulfone), toluene, and toluene diisocyanate is 1-1.5 g: 20-40 mL: 2-2.6 g;

[0022] Step B3: uniformly mix the prepolymer, the intermediate and 2-ethyl-4-methylimidazole, heat the reaction system to 150-160° C., and stir the reaction for 2 hours to obtain a modified toughening agent;

[0023] Furthermore, the usage ratio of the prepolymer, the intermediate and 2-ethyl-4-methylimidazole is 2.06-5.01 g: 2 mol: 0.04-0.14 g.

[0024] A method for preparing a thermally conductive sealant comprises the following steps:

[0025] S1: Mix epoxy resin, diluent and thermal conductive filler, stir at 40-50°C for 20-40min, then add thixotropic agent, curing agent and modified toughening agent, stir at 80-100°C for 1-2h to obtain a mixed material;

[0026] S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 500-1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain a glue liquid;

[0027] S3: grinding the above glue liquid by a sand grinder for 3-4 hours to obtain a thermal conductive sealant.

[0028] Beneficial effects of the present invention:

[0029] The heat-conductive sealant prepared by the invention not only has a good toughening effect and reduces brittleness, but also has excellent heat conductivity and high temperature resistance, thereby extending the service life of the material.

[0030] The thermal conductive filler prepared by the present invention comprises the following steps: firstly, silicon carbide is pretreated with isopropyl alcohol to synthesize a mixture; then, graphene oxide is modified with the mixture by a liquid phase ultrasonic stripping method to synthesize a pre-product; finally, acid-washed nano-diamond is used to prepare a pre-treated nano-diamond with carboxyl groups on the surface; then, the pre-product is reacted with a silane coupling agent to make its surface contain amino groups; then, the amino groups on its surface react with the carboxyl groups of the pre-treated nano-diamond to prepare the thermal conductive filler; in the thermal conductive filler, the nano-diamond not only provides good conditions for heat conduction by virtue of its high thermal conductivity and unique crystal structure, but also its tiny particles can fill the pores of the sealant to enhance the sealing performance; these characteristics effectively prevent the agglomeration and phase separation of the nano-filler, strengthen the interface bonding between the filler and the resin matrix, and comprehensively improve the overall performance; the nano-diamond and As a high-performance hard filler, silicon carbide works synergistically to optimize surface integrity, reduce wear, enhance the wear resistance and thermal conductivity of the sealant, and extend its service life. In addition, as a ceramic material, silicon carbide has corrosion resistance, high oxidation resistance, high thermal conductivity and low thermal expansion coefficient. Its tight lattice structure allows heat to be quickly transferred through vibration and collision between atoms, thereby achieving efficient heat conduction. Silicon carbide can also be dispersed in the resin matrix to form a thermal conductive network chain, providing a continuous thermal conduction path, and significantly improving thermal conductivity. At the same time, its high melting point and high chemical stability enhance the high temperature resistance and aging resistance of the sealant and extend its service life. In addition, graphene oxide, with its lamellar structure, is evenly dispersed in the sealant, which improves the tensile strength, bonding strength and weather resistance, ensuring the stable performance of the sealant in various harsh environments.

[0031] The modified toughening agent prepared by the invention comprises the following steps: firstly, maleic anhydride is imidized by ammonia, then hydroxymethylated by formaldehyde to obtain hydroxyl groups, the hydroxyl groups react with the epoxy group of epichlorohydrin, then treated with NaHCO3 to epoxidize the end of epichlorohydrin, thereby generating an intermediate; secondly, the hydroxyl group of poly(p-phenylene ether sulfone) reacts with the isocyanate group of toluene diisocyanate to form a carbamate bond to obtain a prepolymer; finally, under the catalysis of 2-ethyl-4-methylimidazole, the epoxy group of the intermediate and the isocyanate group at the end of the prepolymer are subjected to addition polymerization to form an oxazolidinone group to synthesize the modified toughening agent. In the modified toughening agent, the maleimide group of the intermediate can enhance the flexibility of the epoxy resin molecular chain due to its flexibility, form an interpenetrating network structure, relieve stress concentration under external force, thereby improving the toughness and impact resistance of the material, and synergistically promote the curing process of the epoxy resin with the hydroxymethyl group; the poly(p-phenylene ether sulfone) hydroxyl group and the isocyanate group form polyurethane. Due to the unique soft and hard segment structure of polyurethane, it has both high strength and high elasticity. After its introduction, it can effectively improve the crosslinking density of epoxy resin, reduce brittleness, and significantly enhance toughness; in addition, poly(p-phenylene ether sulfone) as a high-performance thermoplastic resin has excellent toughness and heat resistance, can reduce the thermal expansion coefficient, curing shrinkage and internal stress of epoxy resin, effectively inhibit crack propagation, enhance bonding strength, and further improve toughness; in addition, the five-membered ring structure of oxazolidinone has a high thermal decomposition temperature, large cohesive energy, and strong carbon-oxygen double bond energy. After being integrated into the epoxy resin, it gives it excellent high temperature resistance and comprehensively improves the comprehensive performance of the sealant. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1: A method for preparing a thermally conductive sealant, comprising the following steps:

[0034] S1: Weigh the raw materials by weight, including 50 parts of epoxy resin, 1 part of diluent, 10 parts of thermal conductive filler (prepared in this embodiment), 2 parts of thixotropic agent, 8 parts of curing agent, and 1 part of modified toughening agent (prepared in this embodiment); mix the epoxy resin, butyl glycidyl ether and thermal conductive filler, stir at 40° C. for 20 min, then add hydrated aluminum silicate, 4,4'-diaminodiphenylmethane and modified toughening agent, stir at 80° C. for 1 h, and obtain a mixed material;

[0035] S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 500r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid;

[0036] S3: grinding the above glue solution with a sand grinder for 3 hours to obtain a thermal conductive sealant;

[0037] The thermally conductive filler is prepared by the following method:

[0038] Step A1: 2 g of silicon carbide and 200 mL of isopropanol were mixed evenly, and after ultrasonic peeling for 12 h, the mixture was centrifuged at 2000 r / min for 15 min to obtain a mixture;

[0039] Step A2: 300 mL of polydimethyldiallylammonium chloride and 0.4 g of graphene oxide were mixed evenly, stirred at room temperature for 12 h, centrifuged at 10000 r / min for 10 min, washed, and then 4.1 g of the mixture was slowly added dropwise for 1 h, and then centrifuged at 2000 r / min for 10 min, and freeze-dried to obtain a pre-product;

[0040] Step A3: 10.3 mL of concentrated sulfuric acid, 3.4 mL of concentrated nitric acid and 5 g of nano-diamond were mixed, heated in a water bath at 75° C. and stirred for 24 h to obtain pretreated nano-diamond; 6 g of the pre-product was dispersed in 9 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 5 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65° C. for 8 h, the pre-treated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a thermal conductive filler;

[0041] The modified toughening agent is prepared by the following method:

[0042] Step B1: 0.362 g of maleic anhydride was placed in a flask, and ammonia was introduced after sealing. When the flask was cooled to room temperature, the introduction of ammonia was stopped, and the temperature was raised to 180°C for reaction for 6 h. After cooling to room temperature, 3.58 g of tetrahydrofuran, 0.08 g of formaldehyde and 0.225 mL of sodium hydroxide were added and mixed evenly, and the mixture was reacted at 30°C for 4 h. The mixture was rotary evaporated, washed and centrifuged, and 0.2 mL of tetrabutylammonium bromide and 5 g of epichlorohydrin were added and mixed. After ultrasonication for 1 h, 0.2 g of NaHCO3 was added, and the mixture was stirred in an oil bath at 90°C for 12 h. The mixture was filtered, rotary evaporated, washed and centrifuged, and dried at 45°C for 24 h to obtain an intermediate.

[0043] Step B2: dehydrating 1 g of poly(p-phenylene ether sulfone) and evacuating under reduced pressure at 110° C. for 2 h, cooling to 60° C., adding 20 mL of toluene and 2 g of toluene diisocyanate under nitrogen protection, mixing evenly, and reacting at 80° C. for 2 h to obtain a prepolymer;

[0044] Step B3: 2.06 g of prepolymer, 2 mol of intermediate and 0.04 g of 2-ethyl-4-methylimidazole were mixed evenly, and then the reaction system was heated to 150° C. and stirred for 2 h to obtain a modified toughening agent.

[0045] Embodiment 2: A method for preparing a thermally conductive sealant, comprising the following steps:

[0046] S1: Weigh the raw materials by weight, including 72 parts of epoxy resin, 2 parts of diluent, 20 parts of thermal conductive filler (prepared in this embodiment), 6 parts of thixotropic agent, 16 parts of curing agent, and 2 parts of modified toughening agent (prepared in this embodiment); mix the epoxy resin, butyl glycidyl ether and thermal conductive filler, stir at 45° C. for 30 min, then add hydrated aluminum silicate, 4,4'-diaminodiphenylmethane and modified toughening agent, stir at 90° C. for 1.5 h, and obtain a mixed material;

[0047] S2: putting the mixed material into a high-speed mixer and stirring it to make glue, the speed is 750r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid;

[0048] S3: grinding the above glue solution with a sand grinder for 3.5 hours to obtain a thermal conductive sealant;

[0049] The thermally conductive filler is prepared by the following method:

[0050] Step A1: 3 g of silicon carbide and 250 mL of isopropanol were mixed evenly, and after ultrasonic peeling for 12 h, the mixture was centrifuged at 2000 r / min for 15 min to obtain a mixture;

[0051] Step A2: 350 mL of polydimethyldiallylammonium chloride and 0.5 g of graphene oxide were mixed evenly, stirred at room temperature for 12 h, centrifuged at 10000 r / min for 10 min, washed, and then 6.8 g of the mixture was slowly added dropwise for 1 h, and then centrifuged at 2000 r / min for 10 min, and freeze-dried to obtain a pre-product;

[0052] Step A3: 11.2 mL of concentrated sulfuric acid, 3.7 mL of concentrated nitric acid and 7 g of nano-diamond were mixed, heated in a water bath at 75°C with stirring for 24 h to obtain pretreated nano-diamond; 7 g of the pre-product was dispersed in 10.5 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 10 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65°C for 8 h, the pre-treated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a thermal conductive filler;

[0053] The modified toughening agent is prepared by the following method:

[0054] Step B1: 0.3715 g of maleic anhydride was placed in a flask, and ammonia was introduced after sealing. When the flask was cooled to room temperature, the introduction of ammonia was stopped, and the temperature was raised to 180°C for reaction for 6 h. After cooling to room temperature, 3.605 g of tetrahydrofuran, 0.09 g of formaldehyde and 0.272 mL of sodium hydroxide were added and mixed evenly, and the mixture was reacted at 30°C for 4 h. The mixture was rotary evaporated, washed and centrifuged, and 0.2 mL of tetrabutylammonium bromide and 5 g of epichlorohydrin were added and mixed. After ultrasonication for 1 h, 0.2 g of NaHCO3 was added, and the mixture was stirred in an oil bath at 90°C for 12 h. The mixture was filtered, rotary evaporated, washed and centrifuged, and dried at 45°C for 24 h to obtain an intermediate.

[0055] Step B2: 1.25 g of poly(p-phenylene ether sulfone) was dehydrated and vacuumed at 110° C. for 2 h, then cooled to 60° C., 30 mL of toluene and 2.3 g of toluene diisocyanate were added under nitrogen protection, mixed evenly, and reacted at 80° C. for 2 h to obtain a prepolymer;

[0056] Step B3: 3.535 g of the prepolymer, 2 mol of the intermediate and 0.09 g of 2-ethyl-4-methylimidazole were mixed evenly, and the reaction system was heated to 155° C. and stirred for 2 h to obtain a modified toughening agent.

[0057] Embodiment 3: A method for preparing a thermally conductive sealant, comprising the following steps:

[0058] S1: Weigh the raw materials by weight, including 95 parts of epoxy resin, 3 parts of diluent, 30 parts of thermal conductive filler (prepared in this embodiment), 10 parts of thixotropic agent, 25 parts of curing agent, and 4 parts of modified toughening agent (prepared in this embodiment); mix the epoxy resin, butyl glycidyl ether and thermal conductive filler, stir at 50° C. for 40 min, then add hydrated aluminum silicate, 4,4'-diaminodiphenylmethane and modified toughening agent, stir at 100° C. for 2 h, and obtain a mixed material;

[0059] S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid;

[0060] S3: grinding the above glue solution by a sand grinder for 4 hours to obtain a thermal conductive sealant;

[0061] The thermally conductive filler is prepared by the following method:

[0062] Step A1: 4 g of silicon carbide and 300 mL of isopropanol were mixed evenly, and after ultrasonic peeling for 12 h, the mixture was centrifuged at 2000 r / min for 15 min to obtain a mixture;

[0063] Step A2: 400 mL of polydimethyldiallylammonium chloride and 0.6 g of graphene oxide were mixed evenly, stirred at room temperature for 12 h, centrifuged at 10000 r / min for 10 min, washed, and then 9.5 g of the mixture was slowly added dropwise for 1 h, and then centrifuged at 2000 r / min for 10 min, and freeze-dried to obtain a pre-product;

[0064] Step A3: 12.1 mL of concentrated sulfuric acid, 4 mL of concentrated nitric acid and 9 g of nano-diamond were mixed, heated in a water bath at 75°C with stirring for 24 h to obtain pretreated nano-diamond; 8 g of the pre-product was dispersed in 12 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 15 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65°C for 8 h, the pre-treated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a thermal conductive filler;

[0065] The modified toughening agent is prepared by the following method:

[0066] Step B1: 0.381 g of maleic anhydride was placed in a flask, and ammonia was introduced after sealing. When the flask was cooled to room temperature, the introduction of ammonia was stopped, and the temperature was raised to 180°C for reaction for 6 h. After cooling to room temperature, 3.63 g of tetrahydrofuran, 0.1 g of formaldehyde and 0.32 mL of sodium hydroxide were added and mixed evenly, and the mixture was reacted at 30°C for 4 h. The mixture was rotary evaporated, washed and centrifuged, and 0.2 mL of tetrabutylammonium bromide and 5 g of epichlorohydrin were added and mixed. After ultrasonication for 1 h, 0.2 g of NaHCO3 was added, and the mixture was stirred in an oil bath at 90°C for 12 h. The mixture was filtered, rotary evaporated, washed and centrifuged, and dried at 45°C for 24 h to obtain an intermediate.

[0067] Step B2: Dehydrate 1.5 g of poly(p-phenylene ether sulfone) and evacuate under reduced pressure at 110° C. for 2 h, cool to 60° C., add 40 mL of toluene and 2.6 g of toluene diisocyanate under nitrogen protection, mix well, and react at 80° C. for 2 h to obtain a prepolymer;

[0068] Step B3: 5.01 g of prepolymer, 2 mol of intermediate and 0.14 g of 2-ethyl-4-methylimidazole were mixed evenly, and then the reaction system was heated to 160° C. and stirred for 2 h to obtain a modified toughening agent.

[0069] Comparative Example 1: This comparative example is a thermally conductive sealant, which differs from Example 3 in that the thermally conductive filler prepared in Example 3 is the same as that of Example 3 using the same amount of nano-aluminum nitride. The rest are the same.

[0070] Comparative Example 2: This comparative example is a thermally conductive sealant, which differs from Example 3 in that an equal amount of polybutadiene is used to replace the modified toughening agent prepared in Example 3, and the rest are the same.

[0071] Performance test: The thermal conductive sealants prepared in Examples 1-3 and Comparative Examples 1-2 were degassed and scraped on a PTFE plate with a thickness of 5 mm and a diameter of 15 mm, and the thermal conductivity was tested using a thermal conductivity meter; the tensile strength was tested using the standard GB / T1040.1-2006, the bending test was performed using GB1042-79, and the friction and wear test was performed using GB3960-83 (the smaller the value of the wear index, the better the wear resistance); the test results are shown in the following table:

[0072] Table 1

[0073]

[0074] It can be seen from the test data in the table that the thermal conductive sealant prepared in Example 1 not only has a good toughening effect and reduces brittleness, but also has excellent thermal conductivity and high temperature resistance, thereby extending the service life of the material.

[0075] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a thermally conductive sealant, characterized in that: The following steps are involved: S1: Weigh the raw materials by weight, including 50-95 parts of epoxy resin, 1-3 parts of diluent, 10-30 parts of thermal conductive filler, 2-10 parts of thixotropic agent, 8-25 parts of curing agent, and 1-4 parts of modified toughening agent; mix the epoxy resin, diluent and thermal conductive filler, stir at 40-50° C. for 20-40 minutes, then add the thixotropic agent, curing agent and modified toughening agent, stir at 80-100° C. for 1-2 hours to obtain a mixed material; S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 500-1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain a glue liquid; S3: grinding the above glue liquid by a sand grinder for 3-4 hours to obtain a thermal conductive sealant.

2. The method for preparing a thermally conductive sealant according to claim 1, characterized in that: The thermally conductive filler is prepared by the following method: Step A1: Silicon carbide and isopropanol were mixed evenly, and after ultrasonic peeling for 12 hours, centrifuged at 2000 r / min for 15 minutes to obtain a mixture; Step A2: polydimethyldiallylammonium chloride and graphene oxide were mixed evenly, stirred at room temperature for 12 hours, centrifuged at 10000 r / min for 10 minutes, washed, and then slowly added the mixture dropwise for 1 hour, centrifuged at 2000 r / min for 10 minutes, and freeze-dried to obtain a pre-product; Step A3: Mix concentrated sulfuric acid, concentrated nitric acid and nano-diamonds, heat and stir in a water bath at 75°C for 24 hours to obtain pretreated nano-diamonds; then disperse the pre-product in NaOH and stir for 12 hours, add 3-aminopropyltriethoxysilane and ethanol and mix, adjust the pH to 5, stir under magnetic suspension at 65°C for 8 hours, then add pretreated nano-diamonds, ultrasonically treat for 2 hours, wash and dry to obtain a thermal conductive filler.

3. The method for preparing a thermally conductive sealant according to claim 2, characterized in that: In step A1, the usage ratio of silicon carbide and isopropanol is 2-4 g: 200-300 mL.

4. The method for preparing a thermally conductive sealant according to claim 2, characterized in that: In step A2, the usage ratio of polydimethyldiallylammonium chloride, graphene oxide and the mixture is 300-400 mL: 0.4-0.6 g: 4.1-9.5 g.

5. The method for preparing a thermally conductive sealant according to claim 2, characterized in that: In step A3, the usage ratio of concentrated sulfuric acid, concentrated nitric acid, nanodiamond, pre-product, NaOH, 3-aminopropyltriethoxysilane and ethanol is 10.3-12.1 mL: 3.4-4 mL: 5-9 g: 6-8 g: 9-12 g: 0.2 mL: 5-15 mL.

6. The method for preparing a thermally conductive sealant according to claim 1, characterized in that: The modified toughening agent is prepared by the following method: Step B1: maleic anhydride is placed in a flask, sealed and ammonia is introduced, when cooled to room temperature, the introduction of ammonia is stopped, and the temperature is raised to 180°C for reaction for 6 hours, and after cooling to room temperature, tetrahydrofuran, formaldehyde and sodium hydroxide are added and mixed evenly, and the mixture is reacted at 30°C for 4 hours, rotary evaporated, washed, centrifuged, tetrabutylammonium bromide and epichlorohydrin are added and mixed, ultrasonicated for 1 hour, and then NaHCO3 is added, and the mixture is stirred in an oil bath at 90°C for 12 hours, filtered, rotary evaporated, washed, centrifuged, and dried at 45°C for 24 hours to obtain an intermediate; Step B2: dehydrating the poly(p-phenylene ether sulfone), and evacuating the mixture under reduced pressure at 110° C. for 2 h, cooling the mixture to 60° C., adding toluene and toluene diisocyanate under nitrogen protection, mixing the mixture evenly, and reacting the mixture at 80° C. for 2 h to obtain a prepolymer; Step B3: The prepolymer, the intermediate and 2-ethyl-4-methylimidazole are mixed uniformly, and then the reaction system is heated to 150-160° C. and stirred for reaction for 2 hours to obtain a modified toughening agent.

7. The method for preparing a thermally conductive sealant according to claim 6, characterized in that: In step B1, the dosage ratio of maleic anhydride, tetrahydrofuran, formaldehyde, sodium hydroxide, tetrabutylammonium bromide, epichlorohydrin and NaHCO3 is 0.362-0.381 g: 3.58-3.63 g: 0.08-0.1 g: 0.225-0.32 mL: 0.2 mL: 5 g: 0.2 g.

8. The method for preparing a thermally conductive sealant according to claim 6, characterized in that: In step B2, the usage ratio of poly(p-phenylene ether sulfone), toluene and toluene diisocyanate is 1-1.5 g: 20-40 mL: 2-2.6 g.

9. The method for preparing a thermally conductive sealant according to claim 6, characterized in that: In step B3, the usage ratio of prepolymer, intermediate and 2-ethyl-4-methylimidazole is 2.06-5.01 g: 2 mol: 0.04-0.14 g.

10. A thermally conductive sealant, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.